Simple Model-Free Controller for the Stabilization of Planetary Inverted Pendulum - Huanhuan Mai; Ying-Jeh Huang; Xiaofeng Liao; Ping-Chou Wu (Journal of Control Science and Engineering)
A simple model-free controller is presented for solving the nonlinear dynamic control problems. As an example of the problem, a planetary gear-type inverted pendulum (PIP) is discussed. To control the inherently unstable system which requires real-time control responses, the design of a smart and simple controller is made necessary. The model-free controller proposed includes a swing-up controller part and a stabilization controller part; neither controller has any information about the PIP. Since the input/output scaling parameters of the fuzzy controller are highly sensitive, we use genetic algorithm (GA) to obtain the optimal control parameters. The experimental results show the effectiveness and robustness of the present controller.